A systematic review examining the impact of redirecting low-acuity patients seeking emergency department care: is the juice worth the squeeze?. Issue 2 (3rd December 2018) - Kirkland, Scott William; Soleimani, Amir; Rowe, Brian H; Newton, Amanda S
Abstract : Objectives: Diverting patients away from the emergency department (ED) has been proposed as a solution for mitigating overcrowding. This systematic review examined the impact of interventions designed to either bypass the ED or direct patients to other alternative care after ED presentation. Methods: Seven electronic databases and the grey literature were searched. Eligible studies included randomised/controlled trials or cohort studies that assessed the effectiveness of pre-hospital or ED-based diversion interventions. Two reviewers independently screened the studies for relevance, inclusion and risk of bias. Pooled statistics were calculated as relative risks (RR) with 95% confidence intervals (CI) using a random effects model. Results: Fifteen studies were included evaluating pre-hospital (n=11) or ED-based (n=4) diversion interventions. The quality of the studies ranged from moderate to low. Patients deemed suitable for diversion among the pre-hospital studies (n=3) ranged from 19.2% to 90.4% and from 19% to 36% in ED-based studies (n=4). Of the eligible patients, the proportion of patients diverted via ED-based diversion tended to be higher (median 85%; IQR 76–93%) compared with pre-hospital diversion (median 40%; IQR 24–57%). Overall, pre-hospital diversion did not decrease the proportion of patients transferred to the ED compared with standard care (RR 0.92; 95% CI 0.80 to 1.06). There was no significant decrease in subsequent ED utilisation among patients diverted via pre-hospital diversion compared with non-diverted patients (RR 1.09; 95% CI 0.99 to 1.21). Of the three pre-hospital studies completing a cost analysis, none found a significant difference in total healthcare costs between diverted and non-diverted patients. Conclusion: There was no conclusive evidence regarding the impact of diversion strategies on ED utilisation and subsequent healthcare utilisation. The overall quality of the research limited the ability of this review to draw definitive conclusions and more research is required prior to widespread implementation.